Effects of Synchronization of Carbohydrate and Protein Supply in Total Mixed Ration with Korean Rice Wine Residue on Ruminal Fermentation, Nitrogen Metabolism and Microbial Protein Synthesis in Holstein Steers - Min Yu Piao; Hyun J. Kim; J. K. Seo; T. S. Park; J. S. Yoon; K. H. Kim; Jong K. Ha (Asian-Australasian Journal of Animal Sciences, 2012)
Three Holstein steers in the growing phase, each with a ruminal cannula, were used to test the hypothesis that the synchronization of the hourly rate of carbohydrate and nitrogen (N) released in the rumen would increase the amount of retained nitrogen for growth and thus improve the efficiency of microbial protein synthesis (EMPS). In Experiment 1, in situ degradability coefficients of carbohydrate and N in feeds including Korean rice wine residue (RWR) were determined. In Experiment 2, three total mixed ration (TMR) diets having different rates of carbohydrate and N release in the rumen were formulated using the in situ degradability of the feeds. All diets were made to contain similar contents of crude protein (CP) and neutral detergent fiber (NDF) but varied in their hourly pattern of nutrient release. The synchrony index of the three TMRs was 0.51 (LS), 0.77 (MS) and 0.95 (HS), respectively. The diets were fed at a restricted level (2% of the animal’s body weight) in a 3×3 Latin-square design. Synchronizing the hourly supply of energy and N in the rumen did not significantly alter the digestibility of dry matter, organic matter, crude protein, NDF or acid detergent fiber (ADF) (p>0.05). The ruminal NH3-N content of the LS group at three hours after feeding was significantly higher (p<0.05) than that of the other groups; however, the mean values of ruminal NH3-N, pH and VFA concentration among the three groups were not significantly different (p>0.05). In addition, the purine derivative (PD) excretion in urine and microbial-N production (MN) among the three groups were not significantly different (p>0.05). In conclusion, synchronizing dietary energy and N supply to the rumen did not have a major effect on nutrient digestion or microbial protein synthesis (MPS) in Holstein steers.